A Review on SSR Analysis of FACTS Compensated Power System Using Various Control Techniques - Giri, P. D.; Kotwal, C.D. (International Journal of Computer Sciences and Engineering, 2019)
Series Compensation of transmission networks employed with Flexible AC Transmission System device, for transfer of a bulk power, may have to deal with the phenomenon of Sub Synchronous Resonance. The Sub Synchronous Resonance is responsible for generator-turbine shaft damage due to self-excitation, especially in steam and wind turbine power plants, used in radial power systems. After referring about 92, standard research papers, this review paper is prepared, describing the history of Sub Synchronous Resonance problem and basic model developments. The paper demonstrates Induction Generation Effect and Torsional Interaction, both the types of self excitation problems related to Sub Synchronous Resonance. It also demonstrates how the problem of Sub Synchronous Resonance, is dealt in different types of power plants by using Flexible AC Transmission System devices in conjunction with various control techniques. Also some general methods or nonconventional techniques, for SSR mitigation are discussed. The paper is summarizing numerous, Sub Synchronous Resonance analysis techniques and performance of various Flexible AC Transmission System devices for mitigation of sub synchronous oscillations. The paper concludes with scope of research.